NEW VALIDATED METHOD DEVELOPMENT FOR THE ESTIMATION OF SULFAMETHOXAZOLE AND TRIMETHOPRIM IN BULK FORM BY VISIBLE SPECTROSCOPY - Swetha, Gajjela; Kumar, Kusuma Praveen; Sirisha, Kalam (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To develop three novel, sensitive, simple validated visible spectrophotometric methods for the quantitative estimation of sulfamethoxazole (SMZ) and trimethoprim (TMP) in bulk form. Methods: Methods were based on coupling the diazotized aromatic primary amino group of the studied drugs with o-phenylenediamine (OPD) in an acidic medium. The first two methods have been proposed for estimation of SMZ and rest for TMP. The resulting products were measured by spectrophotometric (method I, II and III) tools. The methods were validated as per ICH guidelines. Results: In method I, the absorbance was measured at 482 and 457 nm with linearity ranges of 4.0-40.0 and 5.0-45.0 µg/ml for SMZ. On the other hand, method III was devoted to estimate TMP spectrophotometrically at 457 nm with linearity range of 5-30 μg/ml. The r2 value for all methods were found to be 0.99. The percentage recoveries of SMZ and TMP were found to be 97.98%, 97.56% and 97.55% respectively. The developed methods were subjected to detailed validation procedure in their pure forms. Conclusion: The study concludes that visible spectrophotometric validation methods can be very efficient and economically promising technique for the quantitative analysis of SMZ and TMP in bulk form. The statistical analysis of data indicates that the developed methods were reproducible and specific. It was found that there is a good agreement between the obtained results and those obtained by the reported methods; moreover they can be used for the routine estimations of SMZ and TMP in bulk form.